127k views
3 votes
Solve for Y
y+3x=6
y-5x=-1

User AidanO
by
5.2k points

2 Answers

1 vote
y= 6-3x

replace y with x

(6-3x)-5x=-1
6-3x-5x=-1
-8x=-1
x=-8/-1
x=8

replace x with the solved answer
y+3x=6
y+3*8= 6
y= 6-3*8
y= -21
User KevinBrownTech
by
4.8k points
2 votes
  • y + 3x = 6
  • y - 5x = -1

Isolate y on the right side of the two equations. Subtract 3x from the first equation, and add 5x in the second equation.

  • y = 6 - 3x
  • y = -1 + 5x

Since these two equations both equal y, make them equal to each other in an equation.

  • 6 - 3x = -1 + 5x

Subtract 6 from both sides.

-3x = -7 + 5x

Subtract 5x from both sides.

-8x = -7

Divide both sides by -8.

x = 7/8

  • Plug 7/8 for x into either equation; I will plug it into the first equation.

y + 3(7/8) = 6

  • Multiply 3 * 7/8.

y + 21/8 = 6

  • Subtract 21/8 from both sides.

y = 27/8

User Vanuan
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.